Combined effect of diabetes and frailty on mortality among Chinese older adults: A follow-up study - Shi, Jing; Tao, Yongkang; Wang, Lixiang; Chen, Shuqiang; Zhou, Ziyi; Meng, Li; Zhou, Baiyu; Duan, Chunbo; Xi, Huan; Yu, Pulin (Frontiers in Endocrinology, 2023)
Background: Frailty and diabetes are two important health problems associated with aging in elderly individuals. This paper seeks to analyze the frailty in elderly patients suffering from diabetes and the combined effect of diabetes and frailty on mortality risk. Methods: The frailty index (FI) model was employed when evaluating frailty among the elderly based on the baseline data conducted in 2009; and death as outcome variables collected in 2020 were analyzed. The influence of diabetes on age-related changes in frailty in the elderly and resulting mortality rates was analyzed. Cox regression and Kaplan-Meier curves were applied to evaluate the influence on the risk of death and the 11-year survival of the elderly with varying diabetes and frailty statuses. Results: Ultimately, 1,213 elderly people were included in the analysis, with a total of 447 deaths, and mortality reaching 36.9% by 2020 (447/1,213); there were 271 cases of diabetes, with a prevalence of 22.3% (271/1,213). The mean FI value for elderly patients with diabetes was higher than that of those without regardless of age, and the average annual relative growth rate of the FI value for elderly patients with diabetes was higher than that of those without diabetes (β = 0.039 vs. β = 0.035, t = 8.367, P < 0.001). For all FI value levels, the mortality rate among elderly patients with diabetes was higher than that of those without. The Cox Regression analysis showed that, compared with those suffering from neither diabetes nor frailty, elderly patients with both had the higher mortality risk (HR = 1.760. P < 0.001), followed by elderly patients suffering from frailty alone (HR = 1.594, P = 0.006), and then by elderly patients suffering from only diabetes (HR = 1.475, P = 0.033). The survival analysis showed that the median survival of those suffering from diabetes and frailty to be the shortest at 57.23 (95% CI: 54.05 to 60.41) months. Conclusion: Frailty is common among elderly patients suffering from diabetes, and there is an increased risk of poor health outcomes, such as death, among elderly patients suffering from diabetes and frailty.